2006
DOI: 10.1111/j.1365-2257.2006.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor in proliferation of T lymphocytes in infants with iron deficiency

Abstract: The aim of this study was to contribute to clarify the mechanism of cellular immune insufficiency occurring during iron deficiency. We studied the expression of the transferrin receptor (TfR) which is called as CD71, on the surface of T lymphocytes in infants with iron deficiency (with and without anemia). A total of 33 infants, aged between 7 and 26 months were included in this study. These subjects were divided into three groups: (i) latent iron deficiency (LID) (group 1), (ii) iron deficiency anemia (IDA) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…On the other hand, since exogenous IL-2 did not fully rescue the decreased proliferation of T cells up to the values of the static control cells. CD71 as a late activation marker usually named as membrane glycoprotein transferrin receptor (TfR) that is up-regulated as a mechanism to meet the increased iron demands associated with increased metabolism of activated T cells, and meanwhile to act as a housekeeping receptor that binds iron-loaded transferrin at cell surface and trigger internalization 36,37. Moreover, the newest study demonstrated that CD71 was identified as a novel IKK-binding partner and involved in IKK-NF-κB signaling pathway that exerted transcriptional control over a large number of genes significantly induced during T cell activation 38,39.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since exogenous IL-2 did not fully rescue the decreased proliferation of T cells up to the values of the static control cells. CD71 as a late activation marker usually named as membrane glycoprotein transferrin receptor (TfR) that is up-regulated as a mechanism to meet the increased iron demands associated with increased metabolism of activated T cells, and meanwhile to act as a housekeeping receptor that binds iron-loaded transferrin at cell surface and trigger internalization 36,37. Moreover, the newest study demonstrated that CD71 was identified as a novel IKK-binding partner and involved in IKK-NF-κB signaling pathway that exerted transcriptional control over a large number of genes significantly induced during T cell activation 38,39.…”
Section: Discussionmentioning
confidence: 99%
“…37 Biomarkers that fit currently accepted biological and physiologic paradigms are more readily accepted by the research and clinical communities. 41 TFR2 is also important in regulating iron homeostasis and, interestingly, dysregulated iron homeostasis has been observed in lung allograft patients. 37 Given the profound disturbance that allograft rejection-related processes can have at a cellular and molecular level, it is not surprising that we observed 1,295 probe-sets whose expression levels differ in AR vs NR patients.…”
Section: Integration Of Biological Information and Interpretationmentioning
confidence: 99%
“…Further, patients 39 disruption in iron homeostasis observed in lung allograft patients 40 • TFR2 levels upregulated in activated T cells 41 ; T-cell activation is an expected phenomenon during allograft rejection KLF4 Larger training and testing cohorts would be desirable.…”
Section: Potential Application Of the Biomarker Panel And Caveats Formentioning
confidence: 99%
“…Moreover, it remains unknown about the relationship between CD69 spatial and temporal distribution and CD69 immunoregulatory function. Upon activation, CD71 on T cells is up-regulated as a mechanism to meet the increased iron demands associated with increased metabolism, and meanwhile to act as a housekeeping receptor that binds iron-loaded transferrin at cell surface and trigger internalization[13,14]. However, little is known about how CD71 binds iron-loaded transferrin and mediates endocytosis on cell membrane.…”
Section: Introductionmentioning
confidence: 99%